Encyclopedia of e-health and telemedicine - Cruz-Cunha, Maria Manuela, 1964-; Miranda, Isabel Maria, 1954-; Martinho, Ricardo, 1974-; Rijo, Rui; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This reference features emerging technological developments and solutions within the field of medicine, emphasizing critical research-based articles on digital trends, including big data, mobile applications, electronic records management, and data privacy, and how these trends are being applied within the healthcare sector"--Provided by publisher.
Case studies -- Developments and solutions -- Emerging technologies -- New challenges and issues.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 05/05/2016).
Keywords: Medical care -- Technological innovations -- Encyclopedias; Medical informatics -- Encyclopedias; Biomedical Technology; Telemedicine; Medical Informatics; Cyber-physical systems; Electronic health records; Gamification; Health monitoring; Home healthcare; M-Health; Medical devices; Medical imaging; Technology-assisted medical education; Electronic books; Encyclopedias